Technological change and the labor market : evidence on the impact of the steam engine in late-19th century merchant maritime shipping industry - Neuvonen, Tapani (2018)
The rise in wage inequality in the late-20th century has been widely linked to technological progress and the non-monotonic effect it has on workers of dif-ferent skill levels. Much of the work has been done in the context of recent advances in information and communication technology, which has revolu-tionized work since the 1970s. This Master’s thesis provides information on the impact of the steam engine, which produced wide and long lasting eco-nomic growth from the 19th century to early-20th century. The analysis focuses on high-skilled seamen in the Swedish merchant maritime shipping industry from 1869 to 1914. During this time period steam-powered vessels gradually replace traditional sailing ships.